The control of a state of the static and dynamical posture of a person doing physical exercises - Kashuba, Vitaliy; Loptskyi, Serhii; Lazko, Olha (Journal of Education, Health and Sport, 2017)
Actuality. The huge growth of interest in studying the state of human standing, according to researchers, is the result of epoch-making transformation of the human motor mode. Objectives of research: to provide information about development of diagnostics technologies of the state of the static and dynamic position of a person in the process of physical education. Results of research. Movements are the vital human potential that ensures the normal functioning of its organism as a complex biological system. The human musculoskeletal system performs many functions, the most important of them is to provide protection, support and movement of the body. The static and dynamical posture is characterized by the vertical position of the body, which is in equilibrium while changing it’s posture dynamicly and over time. In this case, the vertical position of the human body is evaluated as a certain harmony of interrelated spatial characteristics of the body. A special place among the methods for assessing the state of static and dynamic posture is videometry. Conclusions. The phenomenon of the human body still attracts the huge attention of researchers. A special place in the reflection of the shape of the human body is the state of static and dynamical posture. The state of static and dynamical posture of a person is a resalt of phylogeny and ontogenesis processes. It should be noted that the active use of videoometry method is very useful while analyzing the diagnostic approaches of static and dynamical posture of a person. The further research will be associated with the development of information and methodological system aimed on measuring the state of spatial organization of the human body in the process of physical education.